Teaching Listening to Improve Oral Communication In EFL Intermediate Classes: Case Study of Two Secondary Schools In Cotonou (Benin) - IWIKOTAN, K. ETIENNE; ZOUNHIN TOBOULA, Coffi Martinien; TOSSOU, Vrai-Amour S.G. (My University, 2021)
Abstract: In the first language acquisition process, children develop the listening skill before other skills. In addition, a human being who is not capable of listening cannot participate in a communication act appropriately. This study investigates the teaching of listening to improve oral communication. Its specific objectives are to determine EFL learners’ difficulties in listening comprehension and to find out strategies used by EFL teachers to develop listening comprehension in their learners. To that effect, a questionnaire was administered to a sample of 23 EFL teachers and another one to 292 learners. The study revealed that difficulties encountered by the learners include the fact that they live in a multilingual environment that has the potential of bringing about linguistic interferences. The learners also experience difficulties decoding their teachers and native speakers and reported that their teachers never assess their listening skill. As far as strategies used by teachers are concerned, they encourage their learners to practice listening at home. They also teach their learners listening processing strategies such as bottom-up and top-down strategies. Finally, the teachers divide their listening lessons into three phases including pre-listening, while-listening, and post-listening phases. Résumé : Dans le processus d’acquisition de la première langue, les enfants développent d’abord l’écoute avant les autres compétences. De plus, un être humain ne peut pas participer adéquatement à un acte de communication sans être en mesure d’écouter. La présente étude explore l’enseignement de l’écoute en vue d’améliorer la communication orale. Elle a pour objectifs spécifiques de déterminer les difficultés auxquels les apprenants de l’anglais langue étrangère (ALE) sont confrontés en matière de compréhension de l’écoute et les stratégies utilisées par les professeurs d’ALE pour amener leurs apprenants à développer la compréhension de l’écoute. À cet effet, un questionnaire a été administré à 23 professeurs d’ALE et un autre à 292 apprenants. L’étude a révélé que les difficultés auxquelles les apprenants sont confrontés comprennent le fait qu’ils vivent dans un environnement multilingue qui est susceptible de créer des interférences linguistiques. Les apprenants ont également du mal à décoder leurs enseignants et les natifs et ils ont signalé que leurs enseignants n’évaluent pas leur compétence en écoute. En ce qui concerne les stratégies utilisées par les enseignants, ils encouragent leurs apprenants à pratiquer la compréhension de l’écoute en dehors de la classe. Ils enseignent également les stratégies de traitement de l’écoute telles que la stratégie descendante ou ascendante. Pour terminer, ils divisent leurs leçons d’écoute en trois phases à savoir la phase de pré-écoute, la phase d’écoute et la phase de post-écoute.
Keywords: Keywords: English as a foreign language; listening comprehension; secondary education; strategies; difficulties; Mots-clés : anglais langue étrangère; compréhension de l’écoute; enseignement secondaire; stratégies; difficultés